1991
DOI: 10.1128/jcm.29.1.158-161.1991
|View full text |Cite
|
Sign up to set email alerts
|

Improved method for the routine identification of toxigenic Escherichia coli by DNA amplification of a conserved region of the heat-labile toxin A subunit

Abstract: This report describes a DNA amplification procedure for routine identification of heat-labile-toxin-producing Escherichia coli. Two oligonucleotide primers were used in a polymerase chain reaction procedure to amplify a highly conserved region of the A subunit of the heat-labile enterotoxin gene. Amplifications were done directly on E. coli colonies from plates when Salmonella, Shigella, or parasite infections were excluded as agents of the severe diarrhea in the patients. The conditions for the polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 19 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…In order to develop a multiplex PCR system for the simultaneous detection of SLTI, SLTII, LTI and STII genes of E. coli cells, several other combinations of primers were tried. After several attempts, it was found that primers SLTI-5/SLTI-3 and SLTII-5/SLTII-3 could be combined with the LTI and STII genes specific primers reported by Victor et al (1991) and Lortie et al (1991) and that the detection specificity of this multiplex system is reliable. Under the PCR conditions described under Materials and Methods, all the cells tested could generate the expected PCR products, i.e.…”
Section: Multiplex Pcr System and Its Detection Sensitivitymentioning
confidence: 94%
See 2 more Smart Citations
“…In order to develop a multiplex PCR system for the simultaneous detection of SLTI, SLTII, LTI and STII genes of E. coli cells, several other combinations of primers were tried. After several attempts, it was found that primers SLTI-5/SLTI-3 and SLTII-5/SLTII-3 could be combined with the LTI and STII genes specific primers reported by Victor et al (1991) and Lortie et al (1991) and that the detection specificity of this multiplex system is reliable. Under the PCR conditions described under Materials and Methods, all the cells tested could generate the expected PCR products, i.e.…”
Section: Multiplex Pcr System and Its Detection Sensitivitymentioning
confidence: 94%
“…In addition to the novel PCR primers designed by this laboratory for the detection of the SLTI gene (primer SLTI-5/SLTI-3) and SLTII gene (primer SLTII-5/SLTII-3), PCR primers specific for LTI (primer LT 5-1/LT 3-1) and STII gene (primer STII-FP/STII-RP) reported by Victor et al (1991) and Lortie et al (1991) were used. The sequences, locations within genes, Tm values, and the sizes of PCR products are shown in Table 2.…”
Section: Pcr Primersmentioning
confidence: 99%
See 1 more Smart Citation
“…For the PCR assay, the cell lysate was used as source material and the method of Victor et al . (1991) was modified for cell lysate preparation.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown for other organisms (13,23) and for Mycobacterium spp. (6,19) that PCR amplification can be done successfully on crude sample preparations without prior DNA extraction.…”
mentioning
confidence: 98%